Formulation of biocomposites based on recombinant proteins and plant essential oils for the development of active wound dressings - Gomes, Diana Cristina Serra (2017)
Dissertação de Mestrado em Biologia Molecular, Biotecnologia e Bioempreendedorismo em Plantas